2009
DOI: 10.1253/circj.cj-08-0720
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Patterns of Restenosis After Sirolimus-Eluting Stent Implantation

Abstract: Circ J 2009; 73: 508 -511 lthough drug-eluting stents (DES) have significantly decreased the incidence of restenosis and the need for repeat revascularization, restenosis still occurs. 1-10 Large-scale randomized trials 1-3 have demonstrated a high proportion of focal restenosis after DES implantation, but on the other hand, recent real-world registries have shown that a significant proportion of restenosis is non-focal when DES are used in unselected lesions. [4][5][6][7][8] The present study evaluated angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…In previous studies, predominant of DES restenosis patterns were focal pattern [13,[16][17][18]. Similarly, most of the LR patterns of our study were focal.…”
Section: Discussionsupporting
confidence: 78%
“…In previous studies, predominant of DES restenosis patterns were focal pattern [13,[16][17][18]. Similarly, most of the LR patterns of our study were focal.…”
Section: Discussionsupporting
confidence: 78%
“…Kitahara et al reported 98 cases of focal (79.0%) and 26 of non-focal restenosis (21.0%) among 124 in-stent restenosis lesions after SES implantation, and proximal edge restenosis occurred in 22 lesions (17.7%). 12 When we analyzed the factors associated with edge restenosis after DES implantation, it was significantly related to the angulation at the target lesion site. DES type also seemed to influence the development of edge restenosis, which is thought to be the effect of differences in stent strut thickness and flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been attributed to persistent plaque redistribution or plaque growth. 16, 17 Whether or not W and M develop into significant stent edge stenosis remains to be elucidated.…”
Section: Mechanisms For Formation Of W and Mmentioning
confidence: 99%